Information Theory, Coding and Cryptography. - Saha, Arijit; Manna, Nilotpal; Manna, NilotPal; Mandal, Surajit (2013)
Information Theory, Coding & Cryptography has been designed as a comprehensive text for the students of engineering discussing Source Encoding, Error Control Codes & Cryptography. The book contains the recent developments of coded modulation, trellises for codes, turbo coding for reliable data and interleaving. The text balances the mathematical rigor with exhaustive amount of solved, unsolved questions along with a database of MCQ's.
9.6.5 DES Decryption -- 9.6.6 Strength of DES -- 9.7 Advance Versions of DES -- 9.7.1 Double DES -- 9.7.2 Triple DES -- 9.8 Asymmetric-key Cryptography -- 9.8.1 Public and Private Key -- 9.9 RSA Algorithm -- 9.9.1 Example of RSA -- 9.9.2 Strength of RSA -- 9.10 Symmetric versus Asymmetric-key Cryptography -- 9.11 Diffie-Hellman Key Exchange -- 9.11.1 The Algorithm -- 9.12 Steganography -- 9.13 Quantum Cryptography -- 9.14 Solved Problems -- Multiple Choice Questions -- Review Questions -- Appendix A: Some Related Mathematics -- A.1 Fermat's Little Theorem -- A.2 Chinese Remainder Theorem -- A.3 Prime Number Generation -- A.3.1 Sieve of Eratosthenes -- Bibliography -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books